Soil, water, and nutrients losses as reduced by a growing corn cover - Bertol, Ildegardis; Miquelluti, David José (Pesquisa Agropecuaria Brasileira, 1993)
Soil protection through culture is an effective way to decrease soil erosion. This field experiment was carried out in order to evaluate the effect of one growing season of corn on decreasing losses of water, soil and nutrients under natural rainfall. The treatments (with and without corn) were located on plots with 8,5% of slope, on a clayed soil (Inceptisol) in Lages, SC, Brazil. Soil cover was evaluated with corn relatively to bare soil, both under conventional tillage. Soil, water and nutrients losses were determined on each runoff sampling during the corn season. Corn decreased soil losses by 85% and water losses by 29% relatively to the bare soil. The linear correlation coefficients between soil loss in the bare soil and the rainfall erosivity indexes EI15, EI30, EI45, I15, I30, I45; kinetic energy; total rainfall, and total volume of erosive rainfall were respectively: 0,7053; 0,6968; 0,6785; 0,4847; 0,5274; 0,4870; 0,6018; 0,3922 and 0,5569. The total amount of extractable P and exchangeable Ca+Mg in the runoff was about 3-fold and 8-fold respectively greater on the bare soil compared with the plots where corn was grown; K losses, however, were not different between these two treatments.